Mapping the use of social science in Australian courts: the example of family law children's cases. Issue 3 (2nd July 2016) - Rathus, Zoe
ABSTRACT: This article provides a partial map of the history of the use of social science in children's cases in Australia's family courts. The study was conducted by searching for the names of a range of well-known social scientists, research agencies and social science phrases in the published case databases available from the commencement of the Family Court of Australia in 1976 to the end of 2015. The main focus is on judges' use of social science literature, although the use of unreferenced social science was also rendered visible by the study, as was the use of social science by actors other than judges. The study demonstrates that there is no clear legal principle or doctrine which allows judicial referencing of extrinsic literature in most situations. The results also show that the social science being cited in the courtroom tends to follow what is being discussed in the wider family law community at family law practitioner conferences, at mediation centres and counselling services and in lawyers' offices. However, examination of a number of selected cases suggests that judges might particularly turn to social science literature when the law does not cover the circumstances of the family before them.